Cannabis and COVID-19: Reasons for Concern - van Laar, Margriet W.; Oomen, Pieter E.; van Miltenburg, Charlotte J. A.; Vercoulen, Eefje; Freeman, Tom P.; Hall, Wayne D. (Frontiers in Psychiatry, 2020)
The lockdown measures implemented to curb the spread of SARS-CoV-2 may affect (illicit) drug consumption patterns. This rapid response study investigated changes in cannabis use in a non-probability sample of cannabis users in the Netherlands during the early lockdown period. We fielded an online cross-sectional survey 4-6 weeks after implementation of lockdown measures in the Netherlands on March 15, 2020. We measured self-reported motives for changes in use, and assessed cannabis use frequency (use days), number of joints per typical use day, and route of administration in the periods before and after lockdown implementation. 1,563 cannabis users were recruited. Mean age was 32.7±12.0 years; 66.3% were male and 67.9% used cannabis (almost) daily. In total, 41.3% of all respondents indicated that they had increased their cannabis use since the lockdown measures, 49.4% used as often as before, 6.6% used less often and 2.8% stopped (temporarily). One-third of those who were not daily users before the lockdown became (almost) daily users. Before the lockdown, most respondents (91.4%) used cannabis in a joint mixed with tobacco and 87.6% still did so. Among users of joints, 39.4% reported an increase in the average number consumed per use day; 54.2% stayed the same and 6.4% used fewer joints. This rapid response study found evidence that during the lockdown more users increased rather than decreased cannabis consumption according to both frequency and quantity. These data highlight the need to invest more resources in supporting cessation, harm reduction and monitoring longer term trends in cannabis use.